2022
DOI: 10.1016/j.expthermflusci.2021.110518
|View full text |Cite
|
Sign up to set email alerts
|

Splashing generation by water jet impinging on a horizontal plate

Abstract: The report of COVID-19 virus in municipal wastewater raises the question of whether viruses can become airborne during wastewater transport in sewer systems. The present work experimentally investigates a water jet impinging vertically onto a horizontal plate and the behaviours of the generated tiny droplets. Depending on whether the jet breaks into primary drops before the impingement, three regimes can be defined: non-splashing, jet-splashing and drop-splashing regimes. The splashing ratio, i.e., the portion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
3
12
1
Order By: Relevance
“…. This is comparable to the deposition behavior described for droplets and macroscale jets impacting solids [51,60]. As impact progresses (t = 83 µs), the amplitude of the waves increases and lamella formation is seen (Figure 2, red arrow), sometimes to the point where asymmetric fingering edge formation can be seen, but no secondary droplets detach from the expanding liquid sheet (Figure 2, red circles).…”
Section: Chip Channel Length Filling Levelssupporting
confidence: 82%
See 4 more Smart Citations
“…. This is comparable to the deposition behavior described for droplets and macroscale jets impacting solids [51,60]. As impact progresses (t = 83 µs), the amplitude of the waves increases and lamella formation is seen (Figure 2, red arrow), sometimes to the point where asymmetric fingering edge formation can be seen, but no secondary droplets detach from the expanding liquid sheet (Figure 2, red circles).…”
Section: Chip Channel Length Filling Levelssupporting
confidence: 82%
“…Qian et al reported a jet splashing regime at W e jet = 617 (D jet = 6 mm) [51], almost twice as low compared to our findings (W e jet = 1340). In contrast, Trainer et al saw splashing of jets (D jet = 3 mm) above W e jet = 1500 [63], closer to our findings.…”
Section: Chip Channel Length Filling Levelscontrasting
confidence: 74%
See 3 more Smart Citations